The world city network: national versus global perspective - Stefan Lüthi; Alain Thierstein; Michael Hoyler (European Regional Science Association (ERSA), 2015)
World cities are important nodes in the global networks of knowledge-based economies. As a result of the growing complexity of knowledge creation, firms increasingly organise their activities in business networks that operate across different spatial scales. On the global scale, new information and communication technologies enable the control of business processes across multiple locations. On the regional scale, the advantage of geographical proximity plays an important role. Collective learning processes require a common cognitive, social and cultural context as well as regular face-to-face contacts. Short distances bring people together, thereby stimulating information spillovers and the creation of new ideas. These places of intensive interaction are no longer exclusively located in the traditional inner cities. Rather, they are increasingly found in new urban centres, edge cities, airports or at the stations of high-speed rail networks. The result is a highly polycentric metropolitan system, characterised by accelerated growth in and around smaller cities and towns within the wider metropolitan orbit of one or several big cities. The growth of the knowledge economy has led to new forms of business networks linking cities and towns across different spatial scales. Various attempts have been made to analyse these networks empirically using the interlocking network model of the Globalization and World Cities (GaWC) research network. Two approaches can be distinguished from a spatial perspective: a global approach that studies the world city network from the perspective of the largest advanced producer service firms, and a national approach that starts with the most important knowledge-intensive firms located within specific territorial boundaries. This paper compares the methodological implications and empirical outcomes of both approaches with reference to recent case studies of the German space economy. Both approaches pursue similar objectives: to investigate external relations of German cities, both transnationally and on the national scale. Furthermore, both approaches use the same analytical instrument: the interlocking network model of GaWC. Differences exist in the theoretical argumentation: the global approach is grounded in world city research; the national approach, on the other hand, is anchored in debates in regional science, economic geography and spatial planning. In this paper, we argue for the need of scale-sensitive interpretations of connectivity patterns built by the interlocking network model and conclude with some tentative recommendations for the methodological direction of future research in world city network studies.
Keywords: R12; R58; 330; world city network; Germany; mega-city region; knowledge economy